Al-Diraasaat fi Majaali 'Uluumul Lughah A'rabiyyah wa Ta'Liimiha - Muhammad Jaeni (Jurnal Alsinatuna, 2015)
Study of language is very important in the scientific treasure. In fact, many people showless interest in studying linguistic because it is very complex and it requires a deep study in learningit. Generally, the study of linguistics is classified into two parts; they are theoretical linguistics andapplied linguistics. Theoretical linguistics has many branches including Phonology, Syntax,Morphology, Stylistic, Semantic, and so forth. Meanwhile the branches of applied linguisticsinclude Psycholinguistics, Sociolinguistics, and the methodology of foreign language learning. Thedetail information of those studies requires deep and separate study.